2015
DOI: 10.1002/btpr.2071
|View full text |Cite
|
Sign up to set email alerts
|

Engineering superactive granulocyte macrophage colony‐stimulating factor transferrin fusion proteins as orally‐delivered candidate agents for treating neurodegenerative disease

Abstract: Intravenously injected granulocyte macrophage colony-stimulating factor (GM-CSF) has shown efficacy in Alzheimer's Disease (AD) and Parkinson's Disease (PD) animal studies and is undergoing clinical evaluation. The likely need for dosing of GM-CSF to patients over months or years motivates pursuit of avenues for delivering GM-CSF to circulation via oral administration. Flow cytometric screening of 37 yeast-displayed GM-CSF saturation mutant libraries revealed residues P12, H15, R23, R24, and K72 as key determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…To achieve this, three engineered L. lactis strains are designed to separately produce gamma-aminobutyric acid (GABA), granulocyte-colony stimulating factor (GCSF), or glucagon-like peptide-1 (GLP1) upon blue light exposure. The reason why we choose these three components is that they have been reported to work on anxiety behavior, Parkinson’s disease, and nerve signaling through oral administration. The recombinant bacteria are first delivered to the gut by an small-intestine-targeting and pH-sensitive microsphere system, which is then manipulated by an NIR-light triggered upconversion optogenetic nanosystem.…”
mentioning
confidence: 99%
“…To achieve this, three engineered L. lactis strains are designed to separately produce gamma-aminobutyric acid (GABA), granulocyte-colony stimulating factor (GCSF), or glucagon-like peptide-1 (GLP1) upon blue light exposure. The reason why we choose these three components is that they have been reported to work on anxiety behavior, Parkinson’s disease, and nerve signaling through oral administration. The recombinant bacteria are first delivered to the gut by an small-intestine-targeting and pH-sensitive microsphere system, which is then manipulated by an NIR-light triggered upconversion optogenetic nanosystem.…”
mentioning
confidence: 99%
“…Neuroprotective effects have been observed after recombinant GM‐CSF administration also in a mouse transgenic model of Alzheimer's disease (Kiyota et al, 2018) and a Phase II, placebo‐controlled clinical trial (NCT01409915) has been completed (data not available yet) to assess the efficacy of this drug in 40 patients with Alzheimer's disease. It is worth mentioning that part of the protective effects triggered by GM‐CSF in Alzheimer's disease could be exerted on the bone marrow and not directly in the brain since this cytokine could promote the release of monocytes that could then transmigrate in the CNS and phagocyte amyloid plaques (Heinzelman & Priebe, 2015).…”
Section: Neuroinflammation and Cytokine‐targeted Interventionsmentioning
confidence: 99%
“…GM-CSF promotes the in vitro regeneration of retinal ganglion cells (Legacy et al 2013;Hanea et al 2016), has been shown to have neuroprotective effects in a transient focal cerebral ischemia model in rats (Kong et al 2009), restores motor function in a mouse model of stroke (Shanmugalingam et al 2016;Theoret et al 2016), and provides a neuroprotective response in mouse models of Alzheimer's disease (Boyd et al 2010) and Parkinson's disease (Kim et al 2009;Kosloski et al 2013). GM-CSF may also provide a neuroprotective effect by triggering the entry of microglia, tissue-resident macrophages of the CNS, into the brain across the blood -brain barrier (Boyd et al 2010;Shang et al 2016), suggesting a beneficial role in patients with Alzheimer's disease or Parkinson's disease (Boyd et al 2010;Heinzelman and Priebe 2015).…”
Section: Bc Cytokines In the Nervous Systemmentioning
confidence: 99%